Harmonization of Customary Law and Investment Policy in Indonesian Indigenous Natural Resource Governance - Pahlefi Pahlefi; Eko Nuriyatman; Lili Naili Hidayah; Rika Lestari; Waleed Eid M Aldhafeeri; Khalid Saleh Y Alammari (Faculty of Law Universitas Trunojoyo Madura, 2026)
Agrarian conflicts in Indonesia show the limitations of formal legal approaches in accommodating the rights of indigenous peoples, especially in the context of land-based investment expansion. This article analyzes the interaction between customary norms and investment-based governance of natural wealth through a case study of Jelutih Village, Jambi Province. This study aims to identify the gap between normative recognition and implementive practice, as well as to formulate a more inclusive governance model. This study uses a qualitative approach, with normative juridical methods, strengthened by conceptual analysis and a literature review. The findings show that legal recognition of indigenous peoples remains partial and has not been integrated into resource management operational mechanisms, thereby triggering tenure conflicts and weakening the bargaining position of local communities in the face of investment actors. The novelty of this article lies in the development of an operational legal pluralism framework through three key dimensions, namely: first, the recognition of the collective rights of indigenous peoples; second, the application of the principle of Free, Prior and Informed Consent (FPIC) in the investment process; and third, fair and sustainable distribution of benefits. This framework shifts the position of indigenous peoples from policy objects to major actors in natural resource governance. This article contributes to strengthening the discourse of legal pluralism by offering an integrative model relevant to agrarian policy reform and resource governance at the local and national levels.